Changing consumers and changing technology in health care and health care delivery - Kronenfeld, Jennie J. (Amsterdam ; New York : JAI, 2001)
This text deals with issues of growing importance in both the US health care system and health care systems across the world. Such systems need to respond to changes in technology within health care, shifting technologies not specific to health care, and changes in the way patients and physicians view health and the use of health services in society. Chapters focus on how technologies and programs apply to either general groups within the health care system or more specialized groups, such as people with a certain health care problem. Papers deal with a variety of topics, from a focus on consumers and the varying roles the play in the emerging and changing US health care system, to the examination of specific principles such as social network approaches.
Includes bibliographical references.
Description based on print version record.
Keywords: Social medicine -- United States; Medical technology -- United States; Medical care -- United States; Health systems & services; USA; Medical -- Health Care Delivery